2021
DOI: 10.3390/agronomy11081541
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soil Acidity and Bacterial Wilt Occurrence in Potato Production in Ethiopia

Abstract: Soil acidity is one of the main constraints to crop production worldwide. In Ethiopia, the problem of soil acidity has been increasing. Currently, more than 40% of cultivated land in the country has a soil pH < 5.5. Recently, bacterial wilt (caused by Ralstonia solanacearum) has become a serious problem, reaching epidemic levels in some of the major potato growing districts in the country. However, it is currently unknown if the current outbreak of bacterial wilt in potato production is associated with soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…1 ) with more emphasis in central high lands where major seed potato is being distributed to the country ( Gorfu, Woldegiorgis & Kassa, 2013 ; Abdurahman et al, 2017 ; Sharma et al, 2018 , Tessema et al, 2020 ; 2022 ). The disease transmission was slow and not a plague too many potato farms at a time, so that no one gave due attention to the pathogen and by now it becomes a serious production threat for the farming community ( Gorfu, Woldegiorgis & Kassa, 2013 ; Sharma et al, 2018 ; Tafesse et al, 2021 ). The spread of the disease to different parts of the country was traced from latently infected seed tubers and currently the pathogen is serious constraint to more than 5 million potato farmers of Ethiopia ( CSA, 2018 ; Abdurahman et al, 2017 ).…”
Section: Occurrence and Distribution Of R Solanacearummentioning
confidence: 99%
See 2 more Smart Citations
“…1 ) with more emphasis in central high lands where major seed potato is being distributed to the country ( Gorfu, Woldegiorgis & Kassa, 2013 ; Abdurahman et al, 2017 ; Sharma et al, 2018 , Tessema et al, 2020 ; 2022 ). The disease transmission was slow and not a plague too many potato farms at a time, so that no one gave due attention to the pathogen and by now it becomes a serious production threat for the farming community ( Gorfu, Woldegiorgis & Kassa, 2013 ; Sharma et al, 2018 ; Tafesse et al, 2021 ). The spread of the disease to different parts of the country was traced from latently infected seed tubers and currently the pathogen is serious constraint to more than 5 million potato farmers of Ethiopia ( CSA, 2018 ; Abdurahman et al, 2017 ).…”
Section: Occurrence and Distribution Of R Solanacearummentioning
confidence: 99%
“…Nyawade et al (2016) pointed out incorporating suitable indeterminate legume cover crops such as Dolichs lablab in potato cropping systems enabled to minimize soil and nutrient losses due to erosion. This in turn has effect on soil acidity, which has positive association with bacterial wilt prevalence in potato fields ( Tafesse et al, 2021 ). The study by Mwaniki et al (2017) indicated that rotations involving spring onion with the locally grown cereals such as barley and wheat could be utilized in curbing bacterial wilt in Kenya.…”
Section: Disease Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…is a worldwide plant disease that causes serious damage to important cash crops such as tomatoes and potatoes. 4,5 Nowadays, the means to control crop diseases caused by fungi and bacteria mainly include breeding resistant varieties, using chemical pesticides or improving field management measures. Often the breeding of resistant varieties takes a long time, while the use of chemical pesticides is effective but has caused bacterial resistance, environmental contamination, and ecological and human safety problems.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial wilt caused by the bacterium Ralstonia spp. is a worldwide plant disease that causes serious damage to important cash crops such as tomatoes and potatoes 4,5 . Nowadays, the means to control crop diseases caused by fungi and bacteria mainly include breeding resistant varieties, using chemical pesticides or improving field management measures.…”
Section: Introductionmentioning
confidence: 99%